Human Capital As A Strategic Partner In Organizational Transformation - Putri Selviani; Agnes Noria Nabila Siregar; Dini Wulandari; Dora Iccabella Sitanggang; Nayla Putri Aliska; Putri Citra Nabila; Ely Delvi (Yayasan Multidimensi Kreatif, 2024)
This research discusses the important role of human capital as a strategic partner in the organizational transformation process. In an increasingly complex and dynamic era, organizations are required to adapt quickly through significant changes, both in terms of technology, structure, and culture. Successful organizational transformation depends not only on strategy and technology, but also on the potential and competence of existing human resources. Human capital plays a central role in designing and implementing change, as well as being a key element in achieving the organization's long-term goals. As a strategic partner, human capital helps in formulating policies, strengthening the culture of innovation, and creating synergies that support the sustainability of the organization. This research also identifies the challenges faced in maximizing the role of human capital during the transformation process and offers solutions to mitigate these barriers. With the right approach, human capital can be a very valuable asset in creating a resilient and sustainable organization.